Comparison Performance of Robustness Test using Intelligent Fuzzy based Controller for Simulation Study - Mohd Yusoff, Zakiah; Dalila Khirul Ashar, Nur; Muhammad, Zuraida; Fadzilah Razali, Noor; Azeehan Azli, Shakira; Faiz Zainal Abidin, Amar; Kamaruddin Hasan, Khairul (International Journal of Engineering and Technology, 2018)
This paper presents a comparison simulation performance of robustness test using intelligent fuzzy based controller in extraction process of essential oil. In this study, the control variable is the steam temperature since it gives large effect to quality of essential oil.Â Ideally, the aims of control system applications and design the controllers is to ensure the close loop system satisfies performance criteria such as the system must be stable, minimize the effects of disturbances, good set-point tracking which is rapid and smooth response to set point changes.Â Thus, the robustness test is applied in this study to provide the controller that can produce a smooth control response and also robust to any changes of the operation conditions during running process. The standard performance criteria used to represent dynamic performance are percentage overshoot, rise time, settling time, root mean square error (RMSE) and time on recovering load disturbance. The STFPID controller that was used in controlling steam temperature for extraction process shows the excellent performances based on the result. However, both controllers pass the robustness test with small %OS, RMSE, settling time and rise time.Â Â